Current status of plastic production, prospects and training of manpower in Bangladesh (Journal of Chemical Engineering, 2017)
The main strategy for achieving accelerating growth and reducing poverty, income inequality and regional disparity include creation of productive employment in the manufacturing and organized service sector is to accelerate trade and investment in each and every sector. Development of small and medium enterprises (SMEs) is envisaged as a key element in this strategy. In this aspect, a survey on 43 plastic factories, 5 mold industries, 5 importers of plastic raw materials and machineries, 5 National & International Industries (RMG, Leather and plastic Sectors), 2 Association (BGMEA & BPGMEA) & 3 Government Agencies (Export Promotion Bureau (EPB), Ministry of Labor & Empowerment and Bangladesh Technical Education Board (BTEB)) was conducted on the name of ¡°Need assessment to set-up Bangladesh Institute of Plastic Engineering & Technology (BIPET)¡±. SMEF and BPGMEA offered this study on plastic sector. The plastic factories surveyed included micro, small, medium and large factories. About 80% factories belonged to the SMEs. Technical persons in the Management positions were interviewed using detailed questionnaire. The questionnaire was set to analyze the present status of production process, existing working conditions, hiring trends, education-training-technical skills- working experience of workers and technicians, wages framework, troubleshooting problems, types of machine, technology level, training facilities, need for testing, product quality, research & development facilities, existing factory owner.s qualification, their demand and facing challenges by entrepreneur & future prospect of plastic production in Bangladesh. Key recommendation for the development and future prospect of this sector is to support newly established Bangladesh Institute of Plastic Engineering & Technology under the supervision of BPGMEA and technical assistance from BUET.Journal of Chemical Engineering, Vol. 30, No. 1, 2017: 69-76